Câncer de mama e associação com composição corporal, prática de atividade física, resistência à insulina e perfil lipídico: estudo caso-controle - Mota, Jordana Carolina Marques Godinho (2016)
Breast cancer is the most common nonmelanoma cancer and the leading cause of death among Brazilian women, with multi-causal etiology. Due to its increasing incidence and complexity of the risk factors it aimed at comparing women with and without breast cancer physical activity, body composition, glycemic and lipid profiles in goianas women. This is a case-control study with 90 women newly diagnosed with breast cancer and 164 controls carried out from August / 2014 to January / 2016. Data were collected using a pre-tested and standardized questionnaire, body composition assessed by radiographic absorptiometry method dual beam (DXA) and blood samples were collected to characterize glycemic and lipid profiles. Database was structured in double entry in Epi-InfoTM 2014 and statistical analysis were performed using Stata for Windows (version 12.0). Comparisons of differences in means between groups were analyzed using Mann Whitney U-test for categorical variables we used the chi-square Pearson, later the odds ratio was estimated using logistic regression. The results were divided according to menopausal status. In analyzes by menopausal status it was found that premenopausal women have higher lean body mass percentage and those who were physically active was inversely associated with breast cancer diagnosis. On the other hand, having a high percentage of total body fat and android, assessed by DXA, increased the odds 2.17 (CI 95% = 1.04 - 4.52) and 2.27 (CI 95% = 1.09 4.74) times, respectively. In postmenopausal physically active women reduced the chances in half of having breast cancer (0R = 0.51; CI 95% = 0.29 - 0.92). Among the glycemic profile, lipid and body fat markers were directly linked to breast cancer fasting plasma glucose, insulin, homeostasis model assessment-insulin resistance (HOMA-IR) and Visceral Adiposity Index (VAI). Only HDL cholesterol was inversely associated with breast cancer in the total sample. Physically inactive women with higher conicity index have a greater chance of developing breast cancer. In addition, insulin resistance values above the 50th percentile for the VAI and HDL cholesterol below 50 mg / dL were also associated with breast cancer outcome.